Chapter Introduction Uncomfortable Connections Gender, Memory, War - Gül Altınay, Ayşe (Taylor & Francis, 2016)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book deals with the difficult issue of sexual violence and the complex memory struggles over it. It also deals with the gendered memories of womens active participation in armed forces, whether as part of organized armies or as members of the resistance. The book explores gendered memories of war and conflict through fictionalized and visualized memory narratives in the form of film, literature, photography and art. Finally, it focuses on Feminist Reimaginings, looks simultaneously at the past and future of feminist scholarship on gendered memories of war and political violence, offering thought-provoking self-reflection and imagining new forms of research, writing and analysis. Cynthia Cockburn investigates the afterlife of her previous projects in the former-Yugoslavia, Ireland and Israel/Palestine, exploring new research methodologies, critically analyzing processes of knowledge production, and posing questions regarding the mediation of memories during the research process itself.